Analysis of Supervision Results of Teacher's Performance in Developing Quality of Islamic Education Institutions - Istiqomah Istiqomah; Nurdyansyah Nurdyansyah; Eni Fariyatul Fahyuni; Isa Anshori (Proceedings of The ICECRS, 2020)
Quality human resources will affect the quality of an Islamic educational institution. One of the influential human resources in the development of Islamic educational institutions is the teacher. The principal as the leader of an educational institution is tasked with conducting an assessment of teacher performance. This article aims to explain the importance of teacher performance supervision activities in Islamic education institutions and how the results of teacher performance supervision in developing Islamic education institutions. This research is included in the research with a qualitative approach. It was concluded that the results of supervision of teacher performance are very important in an Islamic educational institution, and the results of supervision of teacher performance can develop the quality of Islamic education institutions.